G329(P) Risk of seizure following zika virus infection in children. (12th March 2018) - Pay, L; Oligbu, O; Fallaha, M; Ahmed, L; Saroey, P; Oligbu, G
Abstract : Introduction: Since 2015, an outbreak of Zika Virus infection (ZiKV) has been reported in over 30 countries. Emerging evidence suggest ZikV causes a spectrum of neurologic diseases both directly and by secondary autoimmunity. In pregnancy, ZiKV is a well-known cause of congenital brain abnormalities, including microcephally, and has been linked with Guillain-Barre syndrome. However, its association with seizures in children is not well described. Methods: We undertook a systematic review of the English literature published from 1947 to August 2017 to evaluate the risk factors, epidemiology, clinical presentation, management and outcomes of seizure following Zika virus infection in children less than 18 years. Data sources included MEDLINE, EMBASE, Cochrane library, and references within identified articles. We also searched the papers using the ISI web of knowledge, to identify relevant articles and conference proceedings. Results: We identified 140 potential studies, of which 8 were duplicate and 122 were excluded on the basis of title and abstracts. A further 2 additional studies did not meet eligibility criteria. Of the 8 eligible studies [3–10], there were 215 with confirmed ZiKV in children less than 18 years by either RT-PCR in plasma, CSF and urine, EEG and MRI while excluding other etiologies. 20% (n=44) cases of had seizure. Among 5 studies reporting clinical characteristics and outcome, the mean age was 5 months (Range 1–8 months) and 75% (n=12/16) of cases were female. All had abnormal neuroimaging (n=44) and responded to anti-convulsant therapy, with no reported mortality. Conclusions and clinical implications: Complications from ZiKV, although uncommon, may be severe. With international spread, clinicians need to be aware that ZiKV may be associated with seizures in children. Therefore, standardising the collection and reporting for individual cases across regions and countries would further allow meaningful analysis of the data collected, enabling monitoring of trends over time.